Direct and spillover effects of biofortified sweetpotato interventions on sustained adoption in Malawi - Gatto, M.; Mgomezulu, W.R.; Okello, J.J.; Pradel, W.; Kwikiriza, N.; Hareau, G. (Elsevier, 2023)
Agriculture-nutrition interventions (ANI) have recently received attention as a promising delivery mechanism for achieving desirable nutritional outcomes. However, more evidence is needed on the effectiveness of such interventions. In this study, we analyze direct and spillover effects of ANIs for biofortified orange-fleshed sweetpotato (OFSP) in Malawi on sustained household outcomes: OFSP adoption, area planted, harvest, and sales. In Malawi, we selected three large-scale OFSP interventions and use a rich dataset of 2,492 smallholder farmers selected from every district of Malawi. Methodologically, we employ bivariate probit, instrumental variables, and propensity score matching techniques. We find positive and sustained participation effects for all outcomes. Second, we find that OFSP interventions spilled over and benefited non-participants who lived in treatment villages. Vine multipliers and vine conservation techniques were key diffusion mechanisms for initial and sustained adoption of OFSP varieties. Interventions promoted higher OFSP root sales which suggests that generating income is an important motivator of adoption, in addition to own-consumption. Also, root sales is an often overlooked diffusion mechanism to reach additional farmers beyond the direct participants. Relevant for policy-makers is that OFSP interventions have sustained positive adoption and diffusion effects, and thus feature well as a relatively cost-effective food-based approach among other strategies to eradicate hidden hunger. Designing ANIs with strong supply-push (e.g., (de)centralized vine multipliers, vine conservation techniques) and demand-pull components (e.g., participatory varietal selection and agronomic training) are key and will need to be accompanied by strategies that create a stronger economic case for OFSP, for instance, by investments to strengthen a processing industry for OFSP roots.